Effects of pentoxifylline on whole blood IL‐2 and IFN‐gamma gene expression in normal dogs. Issue 1 (16th October 2019) - Kummari, Evangel; Gibbs, Andres; Riggs, Caitlin; Fellman, Claire; Stokes, John; Thomason, John; Wills, Robert; Mackin, Andrew; Archer, Todd
Abstract: Background: Pentoxifylline (PTX) is a methylxanthine phosphodiesterase inhibitor that is used as a hemorrheologic and anti‐inflammatory agent in veterinary and human medicine. In human studies, PTX has been shown to decrease T‐cell production of cytokines such as IL‐2 and IFN‐γ. A RT‐qPCR assay to measure activated T‐cell gene expression of IL‐2 and IFN‐γ has been validated in dogs. Objectives: The goal of this study was to utilize this assay to investigate the effects of PTX on in vitro cytokine gene expression in canine whole blood. Methods: Whole blood from seven healthy dogs was collected and incubated with various concentrations of PTX for 1 hr before activation. PTX concentrations spanned and exceeded blood concentrations achieved when administered at clinically relevant dosages (1, 2, 10, 50 and 200 μg/ml). Cyclosporine was used at a concentration of 500 ng/ml as a positive control. All blood samples, including untreated activated baseline samples, were then activated with phorbol myristate acetate and ionomycin for 5 hrs. Results: Analysis of activated whole blood by RT‐qPCR revealed that there was not a significant suppression of IL‐2 or IFN‐γ gene expression at any concentration of PTX when evaluating ΔCt values. All samples exposed to cyclosporine showed significant changes from untreated activated baseline samples, demonstrating marked suppression as the positive control. Cytokine expression, presented as a percentage of untreated activated baseline samples, was also evaluated. After exposure to the highest concentration of PTX (200 μg/ml), median percentage cytokine expression was suppressed to just below 50% of baseline values. This concentration, however, is much higher than blood concentrations reported to be achieved at standardly used pentoxifylline doses. Conclusions: PTX does not appear to significantly suppress T‐cell cytokine production in samples from most dogs at clinically relevant drug concentrations. Further testing is needed to establish the full effects of PTX on the immune system in dogs. Abstract : Pentoxifylline is a methylxanthine phosphodiesterase inhibitor that is used as a hemorrheological and anti‐inflammatory agent in veterinary and human medicine. In human studies, it has been shown to decrease T‐cell production of IL‐2 and IFN‐gamma, but the effects in dogs is unknown. In this in‐vitro study in dogs, pentoxifylline did not appear to significantly suppress T‐cell cytokine production in samples from most dogs at clinically relevant drug concentrations.